Performance analysis of methanol fuelled SI engine with boosted intake pressure and LIVC: A thermodynamic simulation and optimization approach - Kumar Prajapati L.; Vachan Tirkey J.; Raj R.; Jena P.; Giri A. (My University, 2025)
Methanol (CH3OH) is a low-carbon alternative fuel that can be derived through renewable power-to-fuel conversion, offering lower emissions and a higher resistance to knock in SI engines. However, the sole methanol-powered SI engine delivers less brake power. Fuels with a higher calorific value have been blended to solve this problem. However, this may cause overburden with storage, handling, and correct blending (like when methane and hydrogen are blended). To resolve this, this research suggested a novel approach for increasing the power and efficiency of a SI engine using the LIVC (late inlet valve closing) miller cycle and boosted intake pressure under 14 geometrical compression ratio (GCR) with the addition of the start of spark timing (SOI) and equivalency ratio (λ) effects. A quasi-dimensional thermodynamic model (QTDM) was applied to simulate the engine performance with respect to operating variables of 0.6–1.0 λ, 35.50 ––650 aBDC (after Bottom Dead Centre) LIVC timing, 30.00 ––150 bTDC (before Top Dead Centre) SOI Timing and 0.8–1.5 bar intake pressure. After that, design of experiments (DoE) based response surface methodology (RSM) was applied to determine optimum operating setting to maximize power and efficiency and minimize emission and fuel consumption. The results from the RSM illustrate the optimum input parameters to be 0.793 equivalence ratio, 46.900 aBDC-LIVC, 20.750 bTDC-SOI timing, and 1.5 bar intake pressure. Correspondingly, response output performances were found to be 12.36 kW-indicated power (IP), 11.20 kW- brake power (BP), 43.32 % indicated thermal efficiency (ITE), 39.32 % brake thermal efficiency (BTE), 9150.6 kJ/kWh brake specific energy consumption (BSEC), and 0.3 V%- carbon mono oxide (CO), 1247.8 ppm-nitric oxide (NO) emission at exhaust valve opening (EVO). The ANOVA regression models resulted in 95 % accuracy in forecasting output response and composite desirability of optimization of 0.83. Overall, it was found that miller-based LIVC and boosted intake pressure considerably improve the performance of SI engines, and the results projected would be helpful for further study and industry application. © 2024 Elsevier Ltd